Économie politique de la santé comme bien public mondial - Bruno Boidin (Revue de la Régulation)
This paper explores the relevance of the notion of global public good applied to health. The first section investigates the conceptual ambiguity of health as a global public good. Outlining the coexistence of three approaches, the second section analyses the prescriptive ambiguity. The third section examines the causes of the absence of a common project in the field of health as a global public good.